Autophagy Dysfunction in a Diabetic Peripheral Neuropathy Model. Issue 2 (11th November 2022) - Choi, Su-Jeong; Kim, Sena; Lee, Won Suk; Kim, Dong Woon; Kim, Cuk-Seong; Oh, Sang-Ha
Abstract : Background: The relationship between autophagy and diabetic peripheral neuropathy (DPN) has been highlighted in few reports. Using an animal model, the authors investigated the relationship between autophagy and DPN, focused particularly on changes in autophagy in Schwann cells. Methods: The ultrastructural features of DPN mice were evaluated in vivo using transmission electron microscopy. Dysfunction of autophagy in DPN was evaluated using immunofluorescence microscopy and Western blot analysis of proteins related to autophagy, including Beclin1, LC3, and p62. Reactive oxygen species levels were measured in vitro in glucose-treated Schwann cells. Dysfunction of autophagy in glucose-treated Schwann cells was examined by immunofluorescence microscopy and Western blot analysis. Results: Reduced myelin thickness and axonal shrinkage were observed in the sciatic nerves of DPN mice. Reactive oxygen species levels were increased in Schwann cells treated with high glucose ( P < 0.05). The expression of Beclin1 was increased in DPN mice and Schwann cells treated with high glucose ( P < 0.05), whereas the expression of LC3-II/LC3-I ratio and p62 were decreased in DPN mice and Schwann cells treated with high glucose ( P < 0.05). Conclusions: These results suggest that increased levels of reactive oxygen species induced by high glucose may contribute to autophagy dysfunction in Schwann cells. Autophagy dysfunction especially in Schwann cells may be an underlying cause of DPN. Clinical Relevance Statement: This study presents the pathological mechanism of diabetic peripheral neuropathy.